Elemen Pengetahuan Literasi Karbon dalam kalangan Pelajar Sekolah Menengah: Pendekatan Analisis Pengesahan Faktor (CFA): Carbon Literacy Knowledge Element among Secondary School Student: Confirmatory Factor Analysis Approach (CFA) - Norkhaidi, Saiyidatina Balkhis; Mahat, Hanifah; Hashim, Mohmadisa; Nayan, Nasir; Saleh, Yazid (GEOGRAFI, 2017)
Developing a post-carbon society requires the exposure on carbon literacy to increase the knowledge and awareness on keeping environment in order to reduce the negative impact towards environment. Therefore, this study aimed to examine the confirmatory factor for carbon literacy knowledge among secondary school students. Respondents consist of 105 secondary school students in Mualim District, Perak by using simple random sampling. The questionnaire with 1 until 5 level Likert scale was used to get the response. Overall, the questionnaire achieved acceptable reliability with Cronbach alpha values for each variable is greater than .70 and meet the test of normality. Then, the data obtained was processed through exploratory factor analysis (EFA) to observe the factor structure of carbon literacy knowledge. Next, confirmatory factor analysis (CFA) was also conducted to validate the accumulated variable. In conclusions, the findings from both analyses have identified and validated the four key factors in students’ carbon literacy knowledge from 20 questionnaire item, namely (i) Green House Effect, (ii) Carbon Footprint, (iii) Travel Mode, (iv) Air Pollution and (v) Electrical Saving which were learned formally in school. The finding also indicate a fit indices value is equal to p = .000, the relative value of chi-square equivalent to 3.810, .918 to the GFI, .877 for the CFI, .846 for the TLI and RMSEA equals .078. Therefore, the five factors set out should be emphasized in the construction of instruments for advanced research in addition to emphasizing the element carbon literacy obtained in the form of informal education at home and in social media.